Accessibility of Antiretroviral Treatment (ART) services in Nepal - Thapa, Kiran (Health for All, 2015)
Antiretroviral treatment (ART) services have been proved to be very effective in treatment and prevention of HIV/AIDS worldwide. This paper is aimed at whether ART services in Nepal are accessible to people living with HIV (PLHIV) and also tries to explore some barriers to accessibility of ART services. It has been more than a decade since ART services have been started in Nepal. But still, it has not been able to reach all the people who are eligible for treatment. Despite numerous efforts from government and non-government sectors, socio-cultural and managerial issues limit PLHIV’s access to ART services. Health for All Vol.2 2014: 15-17